2014
DOI: 10.1111/jai.12518
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study for phenotypic description of vertebral abnormalities in triploid trout subjected to prolonged deficiency in phosphorus

Abstract: Summary In trout farmed in freshwater, the use of low phosphorus diet and other concurrent changes in food formulations could affect the normal growth of the skeleton and enhance the occurrence of vertebral abnormalities. Hence, it is important to refine diagnostic of malformations to quickly detect signs of P deficiency during production. Two practical diets consisting of P‐deficient (0.5% total P) and P‐sufficient (0.9% total P) were formulated. Experiments were conducted on all‐female juvenile triploid rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The research found that P deficiency decreased final length and weight significantly, and increased feed conversion in early P-deficient when compared to P-sufficient trout. However, 107 days of late P deficiency did not affect final length and weight significantly (Deschamps et al 2014). The initial body weight in the present study was about 40~45 g, while in many of the previous studies, fish used in the experiments were less than 10 g (Roy & Lall 2003;Mai et al 2006;Zhang et al 2006;Shao et al 2008;Sukumaran et al 2009;Luo et al 2010;Xie et al 2011;Yuan et al 2011;Liang et al 2012;Yu et al 2013), which should be more sensitive to P supplement.…”
mentioning
confidence: 95%
“…The research found that P deficiency decreased final length and weight significantly, and increased feed conversion in early P-deficient when compared to P-sufficient trout. However, 107 days of late P deficiency did not affect final length and weight significantly (Deschamps et al 2014). The initial body weight in the present study was about 40~45 g, while in many of the previous studies, fish used in the experiments were less than 10 g (Roy & Lall 2003;Mai et al 2006;Zhang et al 2006;Shao et al 2008;Sukumaran et al 2009;Luo et al 2010;Xie et al 2011;Yuan et al 2011;Liang et al 2012;Yu et al 2013), which should be more sensitive to P supplement.…”
mentioning
confidence: 95%
“…The increased P demand of S. salar after smoltification is well documented (Albrektsen et al , ; Fjelldal et al , ), and several types of skeletal deformities, diagnosed on radiographs, have been related to dietary P deficiency: vertebral body compression, abnormal softness and structural distortion (Baeverfjord et al , ; Sullivan et al , 2007 a , b ; Fjelldal et al , ). Deschamps et al () observed on X‐rays from P‐deficient rainbow trout Oncorhynchus mykiss (Walbaum 1792) decreased intervertebral spaces, homogenous compression of vertebral bodies, a combination of abnormalities, irregular compression and undersized vertebral bodies. Also, hyper radio‐dense vertebral bodies have been linked to mineral deficiency due to the development of ectopic cartilage in bone marrow spaces (Helland et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased efficiency in P use must, of course, not come at the expense of animal health and welfare. Thus, there is a growing demand to increase the digestibility of P in fish diets (Sullivan et al , 2007 a ) and to determine the quantity of dietary P content that is required for healthy growth and healthy skeletal development in farmed fishes (Åsgård & Shearer, ; Roy et al , ; Deschamps et al , ). Greater knowledge of the mechanisms by which P deficiency causes skeletal malformations can contribute to improve the management of P resources in aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Trout were starved 2 days prior to all sampling events. Diet compositions (Table ) were adapted from an open formulation previously developed at Guelph University and successfully tested in our laboratory (Koko et al., ; Deschamps et al., ; Poirier Stewart et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…8 × 10 in., Lot 366018, Kodak Industry, France). As post‐cranial and ural vertebrae can develop abnormalities irrespective to their nutritional condition (Deschamps et al., , ), we focused on caudal vertebrae (V31‐44) using the regionalization proposed by Kacem et al. ().…”
Section: Methodsmentioning
confidence: 99%